2020
DOI: 10.24059/olj.v24i1.2002
|View full text |Cite
|
Sign up to set email alerts
|

Purposeful Interpersonal Interaction: What is it and How is it Measured?

Abstract: Despite extensive studies surrounding the topic of interaction in online learning, faculty are often still relegated to an attempt at replicating their face-to-face course interactions in the online environment. Interpersonal interaction is a necessary yet nebulous concept in online learning. This paper attempts to build a quality lens to view interpersonal interaction in online learning through, called purposeful interpersonal interaction (PII) by exploring types of interpersonal interaction demonstrated in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(128 citation statements)
references
References 30 publications
4
92
0
8
Order By: Relevance
“…The more positive interactions between students-students, students-teachers, and students-content courses, the more successful the teaching and learning will be (Howes et al, 2008;Mashburn et al, 2008). Moreover, recent literature has also suggested that the quality of learning process and daily classroom interactions provide more powerful predictors of students' learning outcomes than other learning components such as class size and students' characteristics (Burchinal et al, 2002;Howes et al, 2008;Mashburn et al, 2008;Mehall, 2020;Wu, Hsiao, & Nian, 2020). The changes of instructional models from a traditional classroom teaching approach to an online classroom teaching also influence the quality of teaching and learning as well as the quality of interactions itself.…”
Section: Literature Review Online and Classroom-based Interaction Quamentioning
confidence: 99%
“…The more positive interactions between students-students, students-teachers, and students-content courses, the more successful the teaching and learning will be (Howes et al, 2008;Mashburn et al, 2008). Moreover, recent literature has also suggested that the quality of learning process and daily classroom interactions provide more powerful predictors of students' learning outcomes than other learning components such as class size and students' characteristics (Burchinal et al, 2002;Howes et al, 2008;Mashburn et al, 2008;Mehall, 2020;Wu, Hsiao, & Nian, 2020). The changes of instructional models from a traditional classroom teaching approach to an online classroom teaching also influence the quality of teaching and learning as well as the quality of interactions itself.…”
Section: Literature Review Online and Classroom-based Interaction Quamentioning
confidence: 99%
“…Students also believed it was critically important to receive prompt and constructive feedback, noting that a “lack of feedback” was “detrimental to their online learning experience” (Tanis 2020 , p. 9). Additionally, students believed that it was important for course instructors to incorporate strategies to engage them with course materials and with their peers in the online learning environment (Bolliger and Martin 2018 ), which creates an opportunity to build community and make sense of what they are learning (Mehall 2020 ). However, during synchronous sessions, students felt that it was not important for course instructors to incorporate various interactive teaching platforms (e.g., Pear Deck, Kahoot, etc.,) to interact with students (Bolliger and Martin 2018 ).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Other classifications include formal and informal interactions (Rhode, 2007), synchronous interaction (such as online chat and video conferencing) and asynchronous interaction (including email, online discussion boards and blogs) (Hines & Pearl, 2004;Croxton, 2014). In addition, a new concept of purposeful interpersonal interaction has been put forward to emphasize the quality of online interaction (Mehall, 2020). An increasing number of interactions do not necessarily lead to a higher quality of online learning; it is therefore important to provide a moderate quantity of high-quality interaction.…”
Section: Background To Online Teaching and Learningmentioning
confidence: 99%